Análisis jurídico a la figura jurídica de la Usura - San Martín Barrera, Jorge Antonio (2013)
The research aims to dispel certain variables with respect to the question asked : "LEGAL LEGAL ANALYSIS TO WEAR FIGURE" will be a thorough analysis of the wedges and legal effects, plus a comparative study of the various laws.